2015
DOI: 10.3844/ajebasp.2015.77.93
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Macroeconomic Variables on Agricultural Diversification in Nigeria

Abstract: Abstract:The study examined the trend in agricultural diversification index from 1960 to 2014 in Nigeria. It also determined the influence of some macroeconomic variables on the estimated index. Augmented Dickey-Fuller-GLS unit root test showed that all series were integrated of order one. The long-run and short-run elasticity of the agricultural diversification index with respect to the specified macro-economic variables were determined using the techniques of co-integration and error correction models. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…While maximum lending rate is the only significant negative driver of agricultural output, the ACGSF loan does not become a positive determinant of agricultural output share until the asymmetric effect of real exchange rate movement was accounted for, though the loan has not yet yielded the desired outcome. As far as the linear relation between exchange rate and agricultural output/exports is concerned, these results gave empirical support to the previous findings of Obayelu and Salau (2010), Omojimite (2014), Akpan et al (2015). In addition, though the effect of real appreciation is larger than the effect of real depreciation, the present study could not find any evidence in support of the asymmetric effect of real exchange rate dynamics on agricultural output performance in the Nigerian economy.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…While maximum lending rate is the only significant negative driver of agricultural output, the ACGSF loan does not become a positive determinant of agricultural output share until the asymmetric effect of real exchange rate movement was accounted for, though the loan has not yet yielded the desired outcome. As far as the linear relation between exchange rate and agricultural output/exports is concerned, these results gave empirical support to the previous findings of Obayelu and Salau (2010), Omojimite (2014), Akpan et al (2015). In addition, though the effect of real appreciation is larger than the effect of real depreciation, the present study could not find any evidence in support of the asymmetric effect of real exchange rate dynamics on agricultural output performance in the Nigerian economy.…”
Section: Discussionsupporting
confidence: 71%
“…Brownson et al (2003) showed that in both long run and short run, real exports, real external reserves, inflation, and external debt have significant negative effects on agricultural productivity, whereas industrial capacity utilization and nominal exchange rate promote agricultural productivity in Nigeria. On the other hand, Akpan et al (2015) reported that longrun positive drivers of agricultural diversification include inflation, viable manufacturing sector, credit to agricultural sector, external reserves, per capita income, unemployment and energy consumption, whereas crude oil prices, lending capacity of commercial banks, FDI in agriculture, and non-oil imports constitute negative long-run drivers in the Nigerian economy. Omojimite (2012) found that the volume of credit to agricultural sector, deficit financing and institutional reform positively and significantly affect agricultural output.…”
Section: The Spending Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the few studies on remittances and agricultural productivity globally, only three (Zahonogo, 2011;Akpan et al, 2014;Dedewanou and Kpekou Tossou, 2022) are on countries in SSA and with inconclusive results (see Zahonogo, 2011), using household data from two villages in Burkina Faso found remittances and migration to negatively impact on agricultural productivity. Akpan et al (2014) examine the relationship at the macroeconomic level for Nigeria and find that in the short run remittances have a positive and significant effect on agricultural productivity, but this effect disappears in the long run. A recent study by Dedewanou and Kpekou Tossou (2022) on farming households in Burkina Faso also find that although remittances increase labor input there is a negative relationship between remittances and total agricultural productivity, confirming the findings of Zahonogo (2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, experts have asserted that one of the ways to tackle the issue of food insecurity is to intensify agricultural production (Akpan et al, 2015a;Akpan et al, 2015b). Besides Morris et al (2007) opined that the intensification of crop-based agriculture has been associated with a sharp increase in the use of chemical fertilizer.…”
Section: Introductionmentioning
confidence: 99%